Diffusion-reaction of substrate in immobilized slab biocatalyst for Michaelis-menten kinetics - Jameel, Ahmed Tariq; R Muhamad Fakih, RM Syibli Milasi (IIUM Press, 2011)
The mass transfer effect on the overall reaction rate in a biocatalyst with a slab geometry containing an immobilized enzyme or cells has been investigated theoretically; Michaelis-Menten kinetics was studied. Numerical solution is used to solve the diffusion-reaction problem for Michaelis-Menten kinetics. The numerical scheme used was shooting method employing Runge-Kutta fourth order method for the solution of system of ODE-IVP. The numerical solution was validated by comparing with the exact solutions for the zero and first order reactions. A third order polynomial solution to the differential equation is also proposed. The approximate solution shows close agreement with the numerical solution within the range of parameters of practical significance. The concentration profiles within the catalyst slab were obtained as a function of Thiele modulus which in turn was used to evaluate effectiveness factor.